Effects of dietary organic acids and nature identical compounds on growth, immune parameters and gut microbiota of European sea bass - Busti, Serena (Sci Rep, 2020)
A 71-day study was conducted to explore the effect of increasing dietary levels (0, 250, 500, 1000 mg kg feed(−1); D0, D250, D500 and D1000, respectively) of a blend of microencapsulated organic acids (OA, specifically citric and sorbic acid) and nature identical compounds (NIC, specifically thymol and vanillin), on growth, intestinal immune parameters and gut microbiota (GM) of European sea bass juveniles reared under normal and subsequently suboptimal environmental conditions (high temperature, 30.0 ± 0.4 °C and low oxygen, 4.6 ± 0.6 mg L(−1)). OA and NIC did not promote growth, feed utilisation and feed intake at the inclusion tested but induced a significantly upregulation of IL-8, IL-10 and TGFβ. GM analyzed by next-generation sequencing showed that OA and NIC were able to exert prebiotic properties stimulating the development of beneficial bacteria taxa such as Lactobacillus, Leuconostoc, and Bacillus sp. Picrust analyses displayed a significant potential functional reconfiguration of GM promoting a decrease in inflammation-promoting and homeostatic functions at increasing OA and NIC administration. For the first time on this species the exposure to suboptimal rearing conditions was able to modify GM structure reducing LAB and increasing Proteobacteria, findings which were consistent with the inflammatory process observed at mRNA level.